Effect of Obesity on Labor Inductions With Foley Plus Oxytocin Versus Oxytocin Alone [37M]. (May 2017) - Mackeen, A. Dhanya; Durie, Danielle; Lin, Monique; Huls, C.; Packard, Roger; Sciscione, Anthony
Abstract : INTRODUCTION: To estimate the effect of body mass index (BMI) on labor and delivery outcomes for women induced with an intracervical Foley catheter plus oxytocin versus oxytocin alone after (near) term premature rupture of the membranes (PROM). METHODS: We performed a multicenter, randomized controlled trial of women with singleton gestations greater than or equal to 34 weeks with PROM and an unfavorable cervix (less than or equal to 2 cm dilated/80% effaced). Subjects were randomly allocated to a Foley catheter inflated to 30 mL with concurrent oxytocin infusion or oxytocin infusion alone. Block randomization was employed with stratification by parity, term/preterm and hospital site. Adjusted linear regression analysis revealed a non-significant shorter time to delivery (-55.4 mins, 95% CI -170.8-60.0, P=.349) in the Foley arm as compared to oxytocin arm. This secondary analysis was conducted to evaluate the effect of BMI on outcomes, within treatment groups. RESULTS: We enrolled 201 women and BMI was known for 198 patients. Twenty two had a BMI less than 25, 59 were overweight, 50 were class I obese, 40 were class II obese, and 27 were class III obese. Regardless of the treatment arm, the tests of trend across BMI categories were not significant for interval from induction to delivery, delivery within 24 hours, vaginal delivery within 24 hours, and cesarean delivery rate. CONCLUSION: Obesity did not appear to affect delivery outcomes for women induced after PROM with an intracervical Foley catheter plus oxytocin versus oxytocin alone.